Mapping Informality: A Spatial Error Model of Socio-Economic Influences on Informal Employment in Indonesia - Nafidza Shadrina Diva Aulia; Cahyaning Adi Mukti; Yulianita Putri Pangaribuan; Khusnul Ashar; Axellina Muara Setyanti (Jurnal Ekonomi, Bisnis & Entrepreneurship, 2026)
The informal employment sector remains a dominant part of the labor market in Indonesia, which is influenced by various socioeconomic factors. This study aims to analyze the spatial influence of poverty, education level, and internet access on the distribution of informal employments in 34 provinces in Indonesia using the Spatial Error Model (SEM). The results show significant spatial autocorrelation, especially for poverty and informal workers, which confirms the existence of inter-regional spillover effects. The SEM estimation shows that poverty has a positive and significant effect on the level of informal employment, while higher education levels and internet access significantly reduce the level of informal employment. These findings emphasize the importance of spatially-aware policy interventions in addressing the issue of informal employments. Strengthening education, digital infrastructure, and targeted poverty alleviation programs are important strategies.